Evaluation of analgesic activity of glucose in Swiss Albino mice - S., Velarul; ., Shobnaarani; Vinotha, Sathiya; ., Ponnuswamy (International Journal of Basic & Clinical Pharmacology, 2019)
Background: Pain is the first and foremost symptom which alerts us about the underlying diseases, injuries or inflammation. Varied treatments are followed for pain relief worldwide. Nowadays tramadol, a centrally acting opioid analgesic is used widely. There are evidences that sweet substances like sucrose produce analgesia through endogenous opioid system. Sucrose has been proved to produce analgesic effect in healthy neonates and also in animals. Likewise, analgesic effect of glucose has also been studied but only limited no. of studies available. Methods: Swiss Albino mice of either sex (20-30g) were procured from the central animal house of KFMS and R, Coimbatore. Animals were maintained under controlled temperature and light conditions with food and water ad libitum. Mice were kept in the department to get acclimatized. 24 mice were divided into 4 groups (n=6). Drugs were given orally after 12hours of fasting. Group I was the control. Group II received standard-tramadol (40mg/kg). Group III received glucose (200mg/kg). Group IV received glucose (400mg/kg). Results: The latency period of glucose was significant (p<0.001) compared to controls and standard was significant (p<0.001) when compared to glucose by hot plate method. Conclusions: Analgesic activity of glucose may be due to both central and peripheral inhibition of PG synthesis. This has been proved in previous studies. This study showed that glucose can be used as an add-on in non-diabetic patients with better compliance.